Cost of managing meningitis and encephalitis among adult patients in the United States of America. (June 2018) - Balada-Llasat, J.M.; Rosenthal, Ning; Hasbun, Rodrigo; Zimmer, Louise; Ginocchio, Christine C.; Duff, Steven; Allison, Jessica; Bozzette, Samuel
Abstract: Objective: To determine the associated costs related to the diagnosis and treatment of meningitis and encephalitis (ME) in adult patients in the USA. Methods: A retrospective observational study design was used to assess the use and costs of diagnostic tests and antimicrobial treatment and the total hospitalization costs for adult patients with suspected ME, who received a lumbar puncture procedure during an emergency department visit or during the first two service days of an inpatient stay. Related costs were calculated by timing of lumbar puncture performed and infectious etiology. Results: A total 26 429 adult patients with suspected ME diagnosed between 2011 and 2014 were included in the study. The mean hospitalization cost was $15 572 ± 27 168, with antimicrobial medication cost of $1144 ± 4052 and laboratory test cost of $210 ± 244. The total visit cost increased with delayed lumbar puncture procedure, intensive care unit stay, and if the etiology was fungi, arbovirus, or bacteria. Conclusions: Higher diagnostic and treatment costs are associated with a delayed lumbar puncture procedure, the etiological agent, and the requirement for an intensive care unit stay.